Portfolio of Outpatients Attending Centre for Urban Health, Madhya Pradesh, Central India - Arti Gupta; B. Venkatashiva Reddy; Mukesh Kumar Nagar; Ajeet Chandel; Surya Bali (SAGE Publishing, 2015)
Background: Knowledge on distribution and burden of diseases in a community is essential for planning of public health services. In the absence of information on morbidity profile through community-based surveys, facility-based data provide a good alternative. The aim of this study was to describe the morbidity profile of patients attending the Centre for Urban Health All India Institute of Medical Sciences (AIIMS) Bhopal (CUHA). Methodology: A record-based descriptive study was carried out in the CUHA Bhopal, Madhya Pradesh, Central India. Information on age, gender, residence, new case, and principal diagnosis were extracted from the outpatient registers for the period between January 2014 and December 2014. Only newly registered patients for the study year (2014) were included. Descriptive analysis was done. Results: A total of 6685 new episodes of illnesses were treated. Adults (>15 years) constituted about 85.0%. Overall, the respiratory disorders were the most common (27.2%) followed by the digestive disorders (10.9%), circulatory disorders (9.9%), musculoskeletal disorders (8.8%), and infectious and parasitic disorders (7.4%). Conclusion: This study gives a brief description of the morbidity profile of patients attending a primary health care center over a period of 1 year. This knowledge would help in planning health services to meet the patients' needs and help in training health staff.